'Prejudices are Tyrants of the Soul': Pedagogy and Préjugés in Revolutionary France. (3rd April 2018) - Malcolm, Hannah N.
ABSTRACT: Through an analysis of textbooks, educational pamphlets, and the correspondence and minutes of the Committee of Public Instruction (22 September 1792–26 October 1795), I argue that authors discussing public instruction under the National Convention invoked the dangers of prejudice as a foil against which to articulate their own vision for the Revolution. Rather than passively accepting a definition imposed from above, these authors took advantage of prejudices' discursive flexibility in order to defend their own visions of the Revolution. As manifestations of counter-revolutionary tendencies and heteronomous reason, prejudices were consistently decried as threats to public safety and the project of regeneration, and public instruction was therefore tailored towards combatting them. While prejudices were thus deployed to ensure that complaints or proposals were taken seriously, prejudices also functioned as a derogatory term used to dismiss others' ideas on a philosophical premise so as to avoid the necessity of engaging with them. Although the discussions about public instruction revealed ambitious hopes for preparing society for a glorious future, prejudices represented the fear that the past would be forever haunting them and thwarting their efforts.